“Caracterización de la población canina y felina, y el conocimiento de los pobladores sobre enfermedades zoonóticas en el sector La Ecuatoriana del sur de Quito.” - Salazar Rios, Escarleth Pamela (2023)
With the purpose of characterizing the canine and feline population, and the knowledge of the inhabitants about zoonotic diseases in the La Ecuatoriana sector of southern Quito. 200 surveys were applied to homes randomly, the parameters in the sector indicate a canine-person, feline-person relationship with a total of 260 canines and 86 felines, in the case of canines 31.5% are females, 68.5% are males, in cats 83% are female and 17% are male, of which 90.35% in canines are vaccinated against rabies, in cats 63.9% have the rabies vaccine. The breed that predominates both in canines 33.4% and cats 58.1%, are the mestizos, regarding the sterilization of canines 90.3% are not sterilized and 9.6% are sterilized, in felines 81.3% are not sterilized and 18.6% are sterilized. 95% of canines have internal deworming, and 86% in cats. The levels of knowledge of the population indicate that 68% do not know the definition of zoonosis, 35% do not know any zoonotic disease, and 41.5% attribute the bite or saliva as a mechanism of transmission. After the surveys carried out and the data analysis, it was concluded that most of the population of the La Ecuatoriana sector has a low percentage of knowledge about zoonoses, certain zoonotic diseases, and their forms of transmission, which makes it a risk factor for the population. For this reason, it is essential to reinforce their knowledge about pet-transmitted zoonoses to owners.